Extent of white matter lesions is related to acute subcortical infarcts and predicts further stroke risk in patients with first ever ischaemic stroke. Issue 6 (16th May 2005) - Fu, J H; Lu, C Z; Hong, Z; Dong, Q; Luo, Y; Wong, K S
Abstract : Objective: To investigate whether the extent of white matter lesions (WML) on fluid attenuated inversion recovery (FLAIR) MRI sequences is an independent risk factor for recurrent stroke, and to document the pattern of acute cerebral infarcts using diffusion weighted imaging (DWI) in patients with different severities of WML. Methods: In a prospective cohort study, 228 consecutive stroke patients were studied between 1999 and 2001 in a community hospital. The severity of WML was graded as 0 (no WML), 1 (mild), 2 (moderate), or 3 (severe) according to the FLAIR appearances. DWI was used to document the location and size of the infarct. Results: 31 patients had grade 0 WML, 69 had grade 1, 59 had grade 2, and 69 had grade 3. Age was independently associated with WML on logistic regression analysis (p = 0.0001). Acute cerebral infarcts in deep white matter were correlated with increasing severity of WML. On a median follow up of 23.0 months, life table analysis showed that recurrent stroke was related to the severity of WML (recurrence rate 7.8% in grade 0, 9.3% in grade 1, 17.7% in grade 2, 43.7% in grade 3; p = 0.0001). Survival was reduced in patients with severe WML (p = 0.0068). A Cox proportional hazards model showed WML to be predictive of recurrent stroke (p = 0.000, hazard ratio = 4.177 (95% confidence interval, 2.038 to 8.564)) and also for survival (p = 0.040, hazard ratio = 2.021 (1.032 to 3.960)). Conclusions: Patients with severe leukoaraiosis have increased risk of deep subcortical stroke and a higher risk of recurrent stroke.